Japan's China policy : a relational power analysis - Hagström, Linus (European Institute of Japanese Studies East Asian economics & business series, 2017)
Japan's China Policy understands Japan's foreign policy in terms of power - one of the most central concepts of political analysis. It contributes a fresh understanding to the subject by developing relational power as an analytical framework and by applying it to significant issues in Japan's China policy: the negotiations for a bilateral investment protection treaty and the disputed Pinnacle (Senkaku/Diaoyu) Islands. Hagström demonstrates that Japan exerted power over China in such divergent empirical settings for the most part by using civilian instruments positively.